2019
DOI: 10.5296/ijhrs.v9i1.14225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Authentic Leadership Style on Job Satisfaction: Case of Insurance Sector in Bosnia and Herzegovina

Abstract: Managing good employees in the current competitive business environment is one of the difficulties an organization is facing in order to accomplish their objectives. Having in mind that employees’ feelings, spirit regarding the job, commitment and engagement are among the biggest factors that should never be overlooked by the organization. All of these factors as well as their reactions to various aspects of the job and organization will seriously affect employees’ performance, involvement and engagement. Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The results of the SEM-PLS 3.0 analysis show that only the internalized moral perspectives significantly affect the commitment of teachers, while the other three aspects of effective leadership (self-awareness, healthy communication, and partnership transparency) are not significant The results of this research are consistent with the findings of the Sakic et al (2019) report, which shows that there is a substantial effect of genuine leadership aspects, specifically personal openness and respect of moral standards, in Bosnia and Herzegovina. In addition, honest leaders are said to improve internal morale, staff engagement, and work satisfaction within the company (Miniotaite & Buciuniene, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the SEM-PLS 3.0 analysis show that only the internalized moral perspectives significantly affect the commitment of teachers, while the other three aspects of effective leadership (self-awareness, healthy communication, and partnership transparency) are not significant The results of this research are consistent with the findings of the Sakic et al (2019) report, which shows that there is a substantial effect of genuine leadership aspects, specifically personal openness and respect of moral standards, in Bosnia and Herzegovina. In addition, honest leaders are said to improve internal morale, staff engagement, and work satisfaction within the company (Miniotaite & Buciuniene, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Studies have found that dedicated workers contribute to healthy output and efficiency (Batugal, 2019). Nevertheless, owing to the poor skills of executive management, most workers neglect their emotions, passion, dedication, and participation in their jobs, and this has influenced their organizational success (Sakic, Hadziahmetovic, & Tandir, 2019). This topic of engagement is also important to research, as past studies indicate that credible leadership strategies are recognized as core determinants of the progress and growth of workers and their overall organization (Mohamad, 2013).…”
Section: Research Problemmentioning
confidence: 99%
“…Leadership authentic style is leadership approach based on honesty, integrity and authenticity (Jafri, 2018). This leadership style emphasizes importance of harmony between personality values and leader behavior with organization purpose and member team interests (Sakic et al, 2019). Leader authentic trying to be their real selves and build the strong relationship with members team based on trust, respect, and transparency (Aganović & Aganović, 2022).…”
Section: Leadership Authentic Stylementioning
confidence: 99%
“…Thus, organizational productivity is determined by employees' efforts, attention and engagement. Employee and leaders' behaviours affect productivity; consequently, intelligent business leaders know that happy workers are productive workers and ultimately benefit their companies (Hadziahmetovic et al, 2022;Osborne & Hammoud, 2017;Sakic et al, 2019) The main objectives of the study are to investigate the impact of Authentic leadership on employee engagement and transparent organizational communication. The study also analyzes the impact of transparent communication on employee engagement.…”
Section: Introductionmentioning
confidence: 99%